From future diets to dishes: communicating dietary shift associated with a 1.5°C scenario for Brazil, China, Sweden and the United Kingdom - Lee, Susan; Freer, Muir; Wood, Ruth; Edelenbosch, Oreane; Sharmina, Maria; Doelman, Jonathan; van Vuuren, Detlef; Wilson, Charlie (Frontiers in Sustainable Food Systems, 2023)
The global food system faces mounting challenges due to a growing population, increased demand for meat protein, and a shifting climate. Reducing meat consumption and transitioning to plant-based diets have been proposed to lower greenhouse gas emissions. Integrated Assessment Models (IAMs) are crucial in understanding the magnitude of changes required to achieve greenhouse gas emission reductions consistent with limiting global warming to 1.5°C. However, interpreting the outputs of these models related to dietary change can be challenging for professionals in diet and nutrition. In this analysis, outputs from the Integrated Assessment Model, IMAGE, are employed to develop more salient information on the potential dietary shifts and dish compositions that are consistent with limiting global temperature increases. This is accomplished by creating visualisations of future dishes and emphasising the proportions of meat-and plant-based ingredients within future diets and dishes. This analysis applied the DDDI (Diets, Dishes, Dish Ingredients) communication framework to visualise these outputs. This study demonstrates how the scenario outputs from IMAGE can be communicated more accessibly and used to convert traditional IAM outputs into a more relevant set of information for a wider audience beyond academia concerning potential future food changes needed to comply with the Paris Agreement. Many countries use dietary guidelines to communicate dietary changes, and the visual charts and figures presented in this research can more effectively convey the appearance of a low greenhouse gas diet.